2021
DOI: 10.1097/gox.0000000000003798
|View full text |Cite
|
Sign up to set email alerts
|

Primary and Revision Rhinoplasty: A Single Surgeon Experience and Patient Satisfaction

Abstract: Background: There is minimal information describing the common characteristics among patients seeking primary/revision rhinoplasty. Success is traditionally interpreted from the surgeon's viewpoint, without considering the patient's perspective. The study's aims were to (1) identify/compare anatomic and functional characteristics commonly found in patients seeking primary and revision rhinoplasties;(2) assess patient satisfaction using a survey; and (3) explore whether graft choice (auricular cartilage versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Another study that included the investigation of claims related to blepharoplasty, rhinoplasty, and rhytidectomy showed that 38.6% of cases alleged a lack of informed consent [34] . In a literature review evaluating 24 different consent forms used for rhinoplasty, the authors found that "unsatisfactory results" and "need for revision" were only covered in 83.3% and 75.0% of consent forms, respectively [35] . Despite this, they reported that these complications were among the top 5 cited in literature.…”
Section: Importance Of Pre-op Counseling and Consentmentioning
confidence: 99%
“…Another study that included the investigation of claims related to blepharoplasty, rhinoplasty, and rhytidectomy showed that 38.6% of cases alleged a lack of informed consent [34] . In a literature review evaluating 24 different consent forms used for rhinoplasty, the authors found that "unsatisfactory results" and "need for revision" were only covered in 83.3% and 75.0% of consent forms, respectively [35] . Despite this, they reported that these complications were among the top 5 cited in literature.…”
Section: Importance Of Pre-op Counseling and Consentmentioning
confidence: 99%
“…1,2 Despite its everyday performance, rhinoplasty remains a complicated cosmetic and functional procedure that helps improve nasal respiration and relieve obstruction, with up to 20% of these surgeries requiring subsequent revisions. [3][4][5][6] As such, surgical complications are common and range in severity from a superficial hematoma, and wound infection, to even death. 4 Given the frequency and complexity involved in rhinoplasties, 1-way surgeons may mitigate these risks is by extensively reviewing the current literature and surgical advancements in operative technique before choosing the surgical approach or the type of rhinoplasty needed.…”
mentioning
confidence: 99%
“…[3][4][5][6] As such, surgical complications are common and range in severity from a superficial hematoma, and wound infection, to even death. 4 Given the frequency and complexity involved in rhinoplasties, 1-way surgeons may mitigate these risks is by extensively reviewing the current literature and surgical advancements in operative technique before choosing the surgical approach or the type of rhinoplasty needed. Often surgeons can find these risks within properly conducted randomized control trials (RCTs).…”
mentioning
confidence: 99%
See 1 more Smart Citation